The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3310/pgfar07030
|View full text |Cite
|
Sign up to set email alerts
|

Developing new ways of measuring the quality and impact of ambulance service care: the PhOEBE mixed-methods research programme

Abstract: BackgroundAmbulance service quality measures have focused on response times and a small number of emergency conditions, such as cardiac arrest. These quality measures do not reflect the care for the wide range of problems that ambulance services respond to and the Prehospital Outcomes for Evidence Based Evaluation (PhOEBE) programme sought to address this.ObjectivesThe aim was to develop new ways of measuring the impact of ambulance service care by reviewing and synthesising literature on prehospital ambulance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…The data-set was originally created to develop and test new ambulance service quality and performance measures (11). We obtained permission from NHS Digital to reuse this dataset to identify the rate of subsequent events for patients who are not transported to hospital (Study code: DARS-NIC-315175-P8X6Z-v2 MR1357).…”
Section: Obtaining and Linking Datamentioning
confidence: 99%
“…The data-set was originally created to develop and test new ambulance service quality and performance measures (11). We obtained permission from NHS Digital to reuse this dataset to identify the rate of subsequent events for patients who are not transported to hospital (Study code: DARS-NIC-315175-P8X6Z-v2 MR1357).…”
Section: Obtaining and Linking Datamentioning
confidence: 99%
“…Access to pain management is considered a fundamental human right (Brennan et al, 2019), yet pre-hospital pain management in children is poor (Samuel et al, 2015). This is despite effective pain management being recently identified as a key quality outcome measure for emergency medical (ambulance) services (EMS) (Turner et al, 2019). The management of pain is known to be complex, especially in children, as age, developmental level, cognitive and communication skills, and associated beliefs must be considered (Srouji et al, 2010;Whitley et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A large group of children were excluded for no initial pain score or no second pain score (n=3872) (see Figure 2). This excluded group were significantly younger (median (IQR) 8 years (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) [p<0.0001]), closer to hospital (median travel time minutes (IQR) 17 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) [p<0.0001]), suffered more traumatic pain (n=2801 (72%) [p<0.0001]), were attended by a paramedic more often (n=2815 (73%) [p=0.0046]), were from more deprived areas (median index of multiple deprivation (IQR) 4 (2-7) [p=0.0002]) and received less analgesia (n=1552 (40%) [p<0.0001]) than those included. See Supplementary File for the table of comparison. Index of multiple deprivation scores were available for 1585 (69%) children, with 670 29%having no home postcode documented and 57 (2%) home postcodes being unmatched / erroneous.…”
Section: Insert Table 1 Herementioning
confidence: 99%
“…Pain is "an unpleasant sensory and emotional experience associated with actual or potential tissue damage". [1] Considering access to pain management is a fundamental human right [2] and has recently been identified as a main quality outcome measure for ambulance services in the UK [3], pre-hospital pain management in children is poor. [4] One Australian study found that more than half (55%) of children with severe pain (verbal numeric rating scale 8-10) did not receive any analgesia.…”
Section: Introductionmentioning
confidence: 99%